Offset carbon emissions or pay a price premium for avoiding them? A cross-country analysis of motives for climate protection activities - Claudia Schwirplies; Andreas Ziegler (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
This paper contributes to the economic literature on pure and impure public goods by considering two alternatives for contributing to the public good climate protection: compensating carbon emissions from conventional consumption or paying higher prices for climate-friendly products. We analytically and empirically examine a wide range of motives and their impact on individuals' choice in favor of these two alternatives. Relying on data from representative surveys among more than 2000 participants from Germany and the USA, our results indicate that environmental awareness, warm glow motives, and the desire to set a good example significantly motivate the choice of both climate protection activities in both countries. However, some motives differ considerably between both alternatives and countries. A green identity enhances the willingness to pay a price premium for climate-friendly goods or services in Germany, while social norms seem to be of much higher relevance in the USA. Our results further suggest that the choice of climate protection activities, especially of carbon offsetting, entails a high degree of uncertainty.
Keywords: H41; Q54; Q58; 330; Public good; climate change; climate protection; carbon offsetting; price premium